Natural Products from Marine Fungi (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Marine fungal natural products are well-known as the “blue gold,” as they have been promising leads for drug discovery and development. Even though marine fungi are less explored in comparison to their terrestrial counterparts, a number of useful hits have been obtained from a drug discovery perspective. Topics discussed in this book include a review on novel natural products from extremophilic fungi, secondary metabolites from deep-sea fungi; natural products from fungi in a symbiotic relationship with marine macro-organisms; and bioactive metabolites from sediment-derived fungi. Marine biologists, chemists, and pharmacologists will find the book a good reference material. The book covers various bioactive marine fungal natural products, and it is hoped that this book aids scientists explore fungal chemical diversity.